Kinanthropometric profile of portuguese water polo players - Canossa, S.; Martins, J. F.; Figueiredo, P.; Fernandes, R. J.; Argudo, F. M.; Garganta, J. M. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
Our purpose was to describe physical and training background characteristics of Water Polo players and compare them according to their specialized playing positions. The International Working Group of Kinanthropometry guidelines were followed. A one-way unvaried measure ANOVA with Bonferroni post hoc was used to develop a multiple comparisons procedure between the specialized playing positions (alpha=0.05). It was concluded that the center players presented tendency for the highest values in 8 of the 10 parameters studied. Center backs are older than the drivers and center forwards have a higher BMI than the wingers and the goalkeepers. The somatotype is balanced mesomorph. Center forwards and Drivers tend to get closer endomorphy when compared with the remaining positions.